WebTool: a system to guarantee the quality of services within a web community GirLand - Froner, Barbara (2002)
The creation of a Web community represents for many businesses and organisations an opportunity to introduce new and innovative business models and strategies. In technological terms, the development of a Web site for an online community presents unique challenges principally in terms of managing the interactions among users, and between users and the company. Only through efficient management of these interactions is it possible to overcome the problems arising from the trade-off between the number of members in the community and the standards of quality for the services offered. In this paper we present WebTool, an instrument we developed to support the management of a Web community – GirLand - having a large and very cohesive membership, with the consequent need to manage the growing number of interactions among them.